Combustion performance of bio-gasoline produced by waste fish oil pyrolysis - Goldbach Andrei; Meier Henry França; Wiggers Vinicyus Rodolfo; Chiarello Luana M.; Barros António André Chivanga (Chemical Industry and Chemical Engineering Quarterly, 2022)
Pyrolysis of triglycerides based on biomass was used at a large scale for fuel supply during the world wars. For this study, the bio-oil produced from waste fish oil pyrolysis was fractioned in a distillation column to produce a light fraction cut in the range of gasoline. This biofuel was tested in a motorcycle engine to measure its performance in terms of torque and to analyse its exhaust gas composition. The emissions were assessed by exploring the combustion of a fossil gasoline without additives and with blends of bio-gasoline, BG20 and BG30 fuels, meaning 20 and 30% of bio-gasoline in fossil gasoline, respectively. Results allowed for the identification of the torque and emission gases combinations for each fuel type and the determination that as the percentage of bio-gasoline in the gasoline was increased, the concentration of CO2, CH4, C2H6, C3H8 decreased in direct relation to the engine rotation. The results show that bio-gasoline can be used as an additive of fossil gasoline with gains of performance in terms of torque and lower concentration of CO2 in the emissions. The torque increased from 3.5 to 3.7 N m and from 4.0 to 5.0 N m in fifth gear and at 2000 and 4000 rpm, respectively.